Analisis Perencanaan Perkerasan Kaku ( Rigid Pavement ) Jalan Plosoklaten - Gedangsewu Kabupaten Kediri - Ridwan, Ahmad; Romadhon, Fajar (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2019)
Pavement is one of the elements of road construction is very important in order to smooth the land transportation so as to provide comfort and safety for its users, so it needs to be well planned based on standards and planning criteria applicable in Indonesia. In this research will be discussed about rigid pavement planning analysis for the development of road infrastructure in urban and rural areas, since this road pavement is more able to support heavy vehicle load and resistant to puddles. From the field data that has been collected, and through analysis and calculation of Road Pavement Planning with CBR value of 90% is 3.5%. Average Daily Traffic on the road 1. MPV, sedan, jeep, pick up: 796; mini bus, small truck: 547; bus, truck as 2: 486; truck 3 as, trailer: 51; motorcycle: 11.687; bicycle / pedicab: 288; carts: 5. Concrete used for upper structure using K.350 thick concrete thickness: 19cm; for bottom foundation using K.175 thickness: 10cm; urugan sand under the foundation using a thick A-class aggregate: 5cm. The reinforcement used for the D-13mm lengthened reinforcement, 200mm spacing; D-13mm transverse reinforcement, 400mm spacing; dowel (ruji) D-25mm, length 450mm, distance 300mm; D-16mm tie bar, 600mm long, 750mm rod spacing. Shoulders use 1m option on the right and left side of the road, drainage using U-Ditch height: 70cm and width: 60cm. From the calculation of such analysis the cost of rigid pavement work of Rp. 89.975.955.000,00 or equivalent: Eighty nine billion nine hundred seventy five million nine hundred and fifty five thousand rupiah.